Elijah and Moses in Mark's account of the Transfiguration - Thrall, Margaret Eleanor (New Testament studies, 1970)
The story of the Transfiguration has received some attention in the past few decades, and the significance of Elijah and Moses has not been neglected. But their prominence in the Marcan narrative has not always been sufficiently recognized, and where it has been recognized it does not seem to have been correctly evaluated.